The role of Jordanian civil society institutions in confronting extremism (An imperical study from the point of view of members of Jordanian civil society organizations 2021) - Altorman, Mohammed Oudeh Falah; Almajali, Fayez Abdulqader (Journal of Humanities & Social Sciences, 2022)
This study aimed at identifying the role of Jordanian civil society institutions in confronting extremism from the point of view of it’s members. To achieve this goal, the descriptive analytical approach was used, the study sample consisted of (378) male and female members of Jordanian civil society institutions were randomly selected, the study questionnaire were distributed to them by google documents. The study concluded that there is a high awareness among members of Jordanian civil society institutions of the concept of extremism, and that their view on the role of Jordanian civil society institutions in combating extremism came at a high level, in addition to that there are many challenges faced by Jordanian civil society institutions in combating extremism from the point of view of the study sample, the most important of which is the lack of funding needed to implement initiatives and activities aimed at combating extremism. The results of the study also indicated that there were no statistically significant differences at the significance level (α≥0.05) on the total degree of the role of Jordanian civil society institutions in combating extremism due to gender, age, the years of experience in volunteer work, Job, nor academic qualifications. The study recommended that Jordanian civil society institutions take the initiative in developing a clear and comprehensive strategy to combat extremism in partnership with all other formal and informal sectors.